Forensic comparison of Soil Samples in Omerli Dam by FTIR and ICP-OES - Sevil Atasoy; İkra Sedef Boler; Soner Kızıl (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Soil is a one of the important physical evidence that could be encountered in any objects including car tire, shoes, or clothes. This study presents the comparison of the soils in Ömerli Dam, Istanbul-Türkiye. 35 of soil samples from 7 different regions have been collected around the lake. FTIR and ICP-OES have been utilized for structural analysis and detection of metal contect in soil samples. Moreover, textural analysis, pH, sedimentation, color tests have been systematically investigated. The image of soil samples is also captured under different light of sources by VSC 8000. The outcome shows that discrimination of soil samples could be studied using various techniques including FTIR, textural analysis, metal concentrations and their color. ICP-OES analysis showed that the soil have various elements such as Si, Fe, Mg, Ca, Cu with a different amounts which provide discrimination for soil samples. The natural pH of the samples varied between 6.1 and 8.3 that are from slightly acidic to moderately alkaline character.